Pelaksanaan Perlindungan Hukum Terhadap Anak Sebagai Pelaku Dan Korban Dalam Tindak Pidana Kesusilaan Di Wilayah Hukum Kepolisian Resor Kampar - Bagus, Adimas; Firdaus, Emilda; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Human rights are basic rights that are inherently human, universal, and bestowed by God Almighty. In the protection of human rights, children are also included. A child is a person who is not yet 18 (eighteen) including a child still in the womb. Child protection efforts should begin as early as possible, but the reality is still often heard by the child being the perpetrator and the victim of decency. In Indonesia the government and the police function to make efforts to protect and improve the welfare of children. Based on data obtained from the polar kampar police, Kampar district occupies the first level of moral crime, especially children who commit criminal acts of decency, and the number of cases has always increased in the last three years. In this case relate to the protection of the child who is the perpetrator and the victim in criminal acts committed by the police of Kampar resort. Efforts are made to overcome obstacles from the Implementation of Legal Protection Against Children as perpetrators and Victims in criminal acts in the territory of Kampar Police Resort Law.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied to provide a complete and clear picture of the problem under study. This research was conducted in Kampar Village Resort Police Law whereas population and sample are all parties related to the problem studied in this research, data source used primary data, secondary data, and tertiary data, data collecting technique in this research is done by observation questionnaires, interviews, and literature review.From the results of research problems there are three main things that can be concluded. First, the implementation of legal protection for children as perpetrators and victims in criminal acts of decency, namely in the form of providing protection in accordance with child protection legislation. Second Implementation of Legal Protection Against Children as perpetrators and Victims in criminal acts in the territorial wards of Kampar Police Resort. The three obstacles in the implementation of legal protection of children as perpetrators and victims in criminal acts in the area of police law resort kampar. The writer's suggestion, firstly in providing legal protection of Kampar Resort Police especially PPA unit is expected to continue to maximize the interests of the child, either as the perpetrator or as the victim, so as not to disturbed the psychological of children experiencing legal process; Secondly, Legal protection of children as perpetrators and victims in legal territory The Kampar Resort Police must be carried out as a digression or discretion as soon as possible while the act can be forgiven. Third, the obstacles faced by the Kampar Police Force from the implementation of legal protection of children as perpetrators and victims there are 2 (two) factors that are internal factors and external factors that must be considered as much as possible.Keywords: Kampar District Police- Child Protection as Perpetrators and Victims - Criminal Acts of Decency